2018
DOI: 10.1007/s00428-018-2326-0
|View full text |Cite
|
Sign up to set email alerts
|

Immune cell landscape in therapy-naïve squamous cell and adenocarcinomas of the lung

Abstract: Squamous cell and adenocarcinomas of the lung develop different mechanisms during carcinogenesis to evade attacks of the immune system. Besides the well-known check-point control programmed death 1 and its ligand, many more mechanisms, acting either tumoricidal or in favor of tumor progression, exist. Analysis of the immune cell profiles in resected tissues and bronchoalveolar lavage samples and correlation between them and with overall survival data was performed. In all tumor samples in this study, cells of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…Hernandez-Martinez et al verified the report by Espindola that VISTA plays an immunomodulatory role in human NSCLC, thus implicating its potential as a pivotal therapeutic target [27]. Brcic et al found high numbers of regulatory T cells and VISTA expression on lymphocytes in samples of both squamous cell and adenocarcinomas of the lung [28]. In fact, cases with VISTA expression ≥ 10% had significantly higher numbers of Treg cells, indicating the potential influence of VISTA on immunosuppressive cells.…”
Section: Non-small Cell Lung Cancermentioning
confidence: 71%
“…Hernandez-Martinez et al verified the report by Espindola that VISTA plays an immunomodulatory role in human NSCLC, thus implicating its potential as a pivotal therapeutic target [27]. Brcic et al found high numbers of regulatory T cells and VISTA expression on lymphocytes in samples of both squamous cell and adenocarcinomas of the lung [28]. In fact, cases with VISTA expression ≥ 10% had significantly higher numbers of Treg cells, indicating the potential influence of VISTA on immunosuppressive cells.…”
Section: Non-small Cell Lung Cancermentioning
confidence: 71%
“…The immunohistochemistry was performed on the available tissue samples after surgery following neoadjuvant SBRT-PATHY using antibodies for apoptosis-inducing factor (AIF), CD3, CD4, CD8, CD20, CD56, CD14, CD15, and S100 protein [14] to explore for the activation and modifications within the tumor microenvironment.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, there has been a remarkable association between VISTA expression with EGFR mutation and improved 5-year overall survival (51). In line with this, Brcic et al have shown that VISTA can be overexpressed in the lymphocytes in squamous cells and adenocarcinoma of the lung (71). Furthermore, high VISTA/PSGL1 co-localization has been associated with improved overall survival in non-small cell lung cancer patients (72).…”
Section: Non-small Cell Lung Cancermentioning
confidence: 88%